Investigations on recycled aggregate concrete made using field demolished waste concrete as coarse aggregates - Bhashya, V.; Ramesh, G.; kumar, B.H. Bharat; Iyer, Nagesh R. (Journal of Structural Engineering, 2025)
In the present study, demolition waste is obtained from the portion of a 12 storey office building of age 10 years, which was converted as a shopping complex. Recycled aggregates are prepared by crushing the demolished concrete. Different percentage replacements considered are 0% (control), 50% and 100%. The physical and mechanical properties of natural aggregate and recycled aggregates are characterized. Experimental investigations are carried out to study the mechanical and durability properties of concrete. Compressive strength, split tensile strength, water absorption, sorptivity and chloride ion permeability of concrete made with recycled aggregates are evaluated. A total of 42 cube (100mm), and 63 cylinders (100mm diameter and 200mm height) are used to determine the mechanical and durability properties. Results showed a reduction in strength of concrete with increase in percentage replacement of natural aggregates. Water absorption and chloride ion permeability of recycled aggregate concrete is high when compared to conventional concrete. To satisfy the requirements of sustainability and developing a green concrete with better properties, the possibilities of inclusion of industrial by-products (viz., fly ash and silica fume) as cementitious material is explored. A significant improvement in compressive strength of recycled aggregate concrete with addition of fly ash/silica fume has been obtained. The improvement in split tensile strength was less with addition of fly ash /silica fume, when compared with improvement in compressive strength. Addition of either fly ash or silica fume to recycled aggregate concrete improves resistance to water absorption and chloride ion permeability characteristics of concrete.